2003
DOI: 10.1093/hmg/ddh005
|View full text |Cite
|
Sign up to set email alerts
|

Interference of Crx-dependent transcription by ataxin-7 involves interaction between the glutamine regions and requires the ataxin-7 carboxy-terminal region for nuclear localization

Abstract: Spinocerebellar ataxia type 7 (SCA7) is an inherited neurodegenerative disorder caused by expansion of a polyglutamine tract in the ataxin-7 protein. A unique feature of SCA7 is degeneration of photoreceptor cells in the retina, resulting in cone-rod dystrophy. In an SCA7 transgenic mouse model that we developed, it was found that the cone-rod dystrophy involves altered photoreceptor gene expression due to interference with Crx, a homeodomain transcription factor containing a glutamine-rich region. To determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 42 publications
2
66
1
Order By: Relevance
“…Crx, which is reduced in R7E mice, acts as a critical regulator of both cone and rod photoreceptor genes. Its transcriptional activity was decreased in another SCA7 transgenic mouse model (Chen et al, 2004b), although it was not impaired in the SCA7 knock-in mice (Yoo et al, 2003). Thus, altered Crx expression may contribute to functional changes in both rod and cone photoreceptors in SCA7 disease.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Crx, which is reduced in R7E mice, acts as a critical regulator of both cone and rod photoreceptor genes. Its transcriptional activity was decreased in another SCA7 transgenic mouse model (Chen et al, 2004b), although it was not impaired in the SCA7 knock-in mice (Yoo et al, 2003). Thus, altered Crx expression may contribute to functional changes in both rod and cone photoreceptors in SCA7 disease.…”
Section: Discussionmentioning
confidence: 96%
“…Accumulation of polyQ-ataxin-7 in the retina of these mice results in decreased expression of phototransduction genes [e.g., rhodopsin (Rho), rod transducin (Gnat1) and phosphodiesterase ÎČ (Pdeb)] (Yoo et al, 2003;Helmlinger et al, 2004b). The expression of rod-specific transcriptional regulators, including cone-rod homeobox (Crx) and neural retina leucine zipper (Nrl), is also reduced (La Spada et al, 2001;Chen et al, 2004b;Abou-Sleymane et al, 2006). As mutations in CRX and NRL lead to human retinal dystrophies (Freund et al, 1997;Sohocki et al, 1998;Bessant et al, 1999;Nishiguchi et al, 2004), SCA7 retinopathy may probably be a consequence of the reduced expression of phototransduction genes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that polyQ domains of proteins can interact with other polyQ-containing or glutamine-rich transcription factors (Chen et al , 2004 ). To test for polyQ-polyQ interactions in vivo , we generated a mammalian two-hybrid system…”
Section: Transactivation Via Polyq Interactions Tested In a Mammalianmentioning
confidence: 99%
“…Expansion of the poly-glutamine tract of ataxin-7 is associated with a dominant neurological disorder, spinocerebellar ataxia type 7 (SCA7), which features cone-rod dystrophy-like retinal degeneration similar to the pathology linked to CRX mutations. Animal model studies and in vitro functional analysis suggest that Crx is a STAGA-dependent transcription activator (La Spada et al, 2001;Chen et al, 2004;Palhan et al, 2005). A polyglutamine-expanded ataxin-7 disrupts Gcn5 HAT activity, resulting in hypoacetylation of histones on Crx target genes and transcription impairment in a SCA7 transgenic mouse model.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%